Health inequity: Possibilities of initiating pulmonary telerehabilitation programs for adults with chronic obstructive pulmonary disorders in conflict and low-resourced areas; A mixed-method phenomenological study. - Suad J Ghaben; Arimi Fitri Mat Ludin; Badr Elkholi; Reem Kullab; Majd Al-Hour; Devinder Kaur Ajit Singh (PLoS ONE)
Objective The "triple problems of COPD"-underdiagnosis, underrecognition, and underdevelopment of pulmonary rehabilitation programs-are global. Pulmonary telerehabilitation (PTR) may solve these problems. This study aims to explore the possibility of launching PTR programs for adults in an area of conflict and low resources. Methods A mixed methods convergent design was used to understand outpatient Pulmonary Rehabilitation (PR) unavailability. The medical records of 70 patients with COPD in the Ministry of Health (MoH) chest unit were analysed quantitatively. thirteen patients who received in-hospital physiotherapy were questioned via a structured and validated questionnaire, and 12 healthcare professionals (HCPs) were interviewed. Quantitative data was analyzed descriptively, and inferentially by the SPSS, outlining the means, standard deviations and percentages, and the chi-square, respectively. Qualitative data was analyzed thematically using the NVivo software, and five themes and 25 subthemes were identified. A thematic framework and triangulation model were depicted accordingly. Results Seventy patients with a mean age of 65.3 ± 1.65 years and a mean hospital stay of 4.89 ± 0.392 days were managed with no admission, Physiotherapy (PT) referral, or discharge criteria. Patients reported needing outpatient PR (4.38 ± 1.193) and a willingness to adopt (3.77 ± .832). Interviews with HCP highlighted the environmental and professional challenges, opportunities, and PTR traits. Quantitative and qualitative data triangulation led to the COPD Sequential Triad (CST) theory. Conclusion This study identified the national, institutional, and professional challenges and opportunities of launching PTR programs in conflict and low-resourced areas, including the conflict's consequences, insufficient resources, and absence of a structured healthcare system and clinical practice guidelines. Promoting health equity in such areas necessitates that the international community and institutions isolate the healthcare sector from conflicts and apply more effective strategies. The study also illustrated the characteristics of the intended PTR programs, including mHealth, therapeutic devices, and hybrid programs along with supporting professional organizations' guidelines.